Equol increases cerebral blood flow in rats via activation of large-conductance Ca2+-activated K+ channels in vascular smooth muscle cells. (May 2016) - Yu, Wei; Wang, Yan; Song, Zheng; Zhao, Li-Mei; Li, Gui-Rong; Deng, Xiu-Ling
Graphical abstract: Abstract: The present study was designed to investigate the effect of equol on cerebral blood flow and the underlying molecular mechanisms. The regional cerebral blood flow in parietal lobe of rats was measured by using a laser Doppler flowmetry. Isolated cerebral basilar artery and mesenteric artery rings from rats were used for vascular reactivity measurement with a multi wire myography system. Outward K + current in smooth muscle cells of cerebral basilar artery, large-conductance Ca 2+ -activated K + (BK) channel current in BK-HEK 293 cells stably expressing both human α (hSlo)- and β1-subunits, and hSlo channel current in hSlo-HEK 293 cells expressing only the α-subunit of BK channels were recorded with whole cell patch-clamp technique. The results showed that equol significantly increased regional cerebral blood flow in rats, and produced a concentration-dependent but endothelium-independent relaxation in rat cerebral basilar arteries. Both paxilline and iberiotoxin, two selective BK channel blockers, significantly inhibited equol-induced vasodilation in cerebral arteries. Outward K + currents in smooth muscle cells of cerebral basilar artery were increased by equol and fully reversed by washout or blockade of BK channels with iberiotoxin. Equol remarkably enhanced human BK current in BK-HEK 293 cells, but not hSlo current in hSlo-HEK 293 cells, and the increase was completely abolished by co-application of paxilline. Our findings provide the first information that equol selectively stimulates BK channel current by acting on its β1 subunit, which may in turn contribute to the equol-mediated vasodilation and cerebral blood flow increase.